Understanding Strabismus - Irfan Sameera (Jaypee Brothers Medical Publisher New Delhi, 2014)
The related aspects of diseases and disorders of strabismus are dealt in this book. Each chapter emphasizes in detail on different types, causes, effects, clinical features, diagnosis, examination, symptoms and treatments for strabismus. This can begin as early as in infancy, childhood, or even in adulthood. With early diagnosis and treatment, the problem can usually be corrected. Delayed treatment may lead to permanent vision loss in one eye. An accurate and detailed history and a step-by-step clinical examination not only help in diagnosing the cause of strabismus but also help in outlining a management plan for surgery. Case studies are considered for most of the disorders along with the images for better understanding.
Keywords: Ophthalmology